Daytrips and getaway weekends in the mid-atlantic states / Patricia Foulke, Robert Foulke - Foulke, Patricia [et.al] (1999)
Itineraries, armchair travel, lodging, information, before you go, food, New York City, Long Island and the Hydson River Valley, Western and Central New York, western Pennsylvania, delaware, New Jersey, Washington, D. c., and Virginia